SIMULATION OF CYCLIC VOLTAMMOGRAM OF RUTHENOCENE (Biological Sciences - PJSIR, 2004)
Digital simulation of cyclic voltammogram of ruthenocene in benzonitrile suggests that electrooxidation of ruthenocene at platinum electrode involves a one-electron oxidation. The ruthenium cation presumably combines with ruthenocene in a fast following chemical reaction. The proposed dimeric monocation so, formed shows a one-electron electroreduction at a much lower potential.